Lack of DNA damage induced by fluoride on mouse lymphoma and human fibroblast cells by single cell gel (comet) assay - Ribeiro, Daniel Araki [UNESP]; Alves de Lima, Patrícia Lepage; Marques, Mariângela Esther Alencar [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (FapUNIFESP (SciELO), 2006)
Fluoride has widely been used in Dentistry because it is a specific and effective caries prophylactic agent. However, excess fluoride may represent a hazard to human health, especially by causing injury on genetic apparatus. Genotoxicity tests constitute an important part of cancer research for risk assessment of potential carcinogens. In this study, the potential DNA damage associated with exposure to fluoride was assessed by the single cell gel (comet) assay in vitro. Mouse lymphoma and human fibroblast cells were exposed to sodium fluoride (NaF) at final concentration ranging from 7 to 100 μg/mL for 3 h at 37μC. The results pointed out that NaF in all tested concentrations did not contribute to DNA damage as depicted by the mean tail moment and tail intensity for both cellular types assessed. These findings are clinically important because they represent a valuable contribution for evaluation of the potential health risk associated with exposure to agents usually used in dental practice.
Keywords: Comet assay; Human fibroblasts; Mouse lymphoma cells; Sodium fluoride; anticaries agent; fluoride sodium; analysis of variance; animal; comet assay; DNA damage; drug effect; fibroblast; genetics; human; lymphoma; mouse; pathology; Analysis of Variance; Animals; Cariostatic Agents; Comet Assay; DNA Damage; Fibroblasts; Humans; Lymphoma; Mice; Sodium Fluoride